Open source systems : enterprise software and solutions : 14th IFIP WG 2.13 International Conference, OSS 2018, Athens, Greece, June 8-10, 2018, Proceedings /: enterprise software and solutions : 14th IFIP WG 2.13 International Conference, OSS 2018, Athens, Greece, June 8-10, 2018, Proceedings. (2018) - Unknown
No abstract available